Assessment of Relationship Between Inflation, Growth and Fiscal Deficit in Albania-An Econometric Approach - Andoni, Mira; Osmani, Myslym (European Scientific Journal, ESJ, 2017)
The relationship between variables growth, inflation and fiscal deficit is largely debated in economic theory; it is studied also empirically. Both theory and ground research suggest negative relationship between growth and inflation, and between inflation and budget deficit, while there is a controversy about relationship between budget deficit and growth. Based on that, IMF suggests programs of macroeconomic stabilization for countries in course of development like Albania. The IMF expertise and support has been available in Albania through bilateral cooperation programs for more than 20 years beginning in 1991. Support of IMF to Albania has been qualified as success. In our research we study the relationship between the three variables, based on Albanian time series data on these variables. We used classical time series regression and stationary time series models, as well ARDL, threshold and switching regression models to investigate these relationships. Our results support the negative relationship between inflation and growth, a positive relationship between inflation and deficit, but we didn’t discover any relationship between fiscal deficit and growth. A threshold nonlinear relationship best describes dependence between growth and inflation.